Purification of African trypanosomes can cause biochemical changes in the parasites - Lonsdale-Eccles, John D.; Grab, D.J. (Wiley, 1987)
Bloodstream forms of African trypanosomes are routinely purified from blood components by a combination of centrifugation and chromatography on DEAE cellulose at pH 8.0, Here we report that the nonphysiological conditions used for DEAE chromatography of the parasites result in changes in the ATP levels of the trypanosomes and an enhanced release from the parasites of proteins such as variable surface glycoprotein, peptidase, and phospholipase. Some of these changes can be reduced by the addition of nucleosides to the elution buffer and, after the elution of the parasites, by immediate readjustment of the external pH to the normal physiological level of blood (pH 7.4).